Understanding the shared epigenetic roots of posttraumatic stress disorder and metabolic syndrome : a DNA methylation study - Toikumo, Sylvanus (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.